2017
DOI: 10.3390/m957
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Bis(2,4,6-trimethylphenyl)-phosphine Oxide

Abstract: Abstract:The single crystal structure of bis(2,4,6-trimethylphenyl)phosphine oxide has been determined. All interatomic distances and angles can be considered normal. The aryl substituents adopt an intermediate configuration when compared to both sterically unhindered (e.g., diphenylphosphine oxide) and congested (e.g., bis(2,4,6-tri-tert-butylphenyl)phosphine oxide) secondary phosphine oxides, illustrating the influence of steric congestion on the molecular structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The number and intensity of 1 H, 13 C, and 31 P resonances confirmed the chemical structure of these compounds. The experimentally determined 1 H– 31 P coupling constants of 1 ( J P‑H = 477.5 Hz), 2 ( J P‑H = 480.0 Hz), and 3 ( J P‑H = 476.0 Hz) and 31 P resonances of 1 (17.73 ppm), 2 (10.48 ppm), and 3 (10.30 ppm) are comparable to the values reported for similar diarylphosphine oxides reported elsewhere (Table S1, ESI). , Diarylphosphine oxides are weak acids and tend to show Ar 2 PO(H)⇌Ar 2 P(OH) tautomerism . The experimentally determined 1 H– 31 P coupling constants and 31 P resonances of 1 , 2 , and 3 indicated that these exist exclusively in the pentavalent Ar 2 PO(H) form.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The number and intensity of 1 H, 13 C, and 31 P resonances confirmed the chemical structure of these compounds. The experimentally determined 1 H– 31 P coupling constants of 1 ( J P‑H = 477.5 Hz), 2 ( J P‑H = 480.0 Hz), and 3 ( J P‑H = 476.0 Hz) and 31 P resonances of 1 (17.73 ppm), 2 (10.48 ppm), and 3 (10.30 ppm) are comparable to the values reported for similar diarylphosphine oxides reported elsewhere (Table S1, ESI). , Diarylphosphine oxides are weak acids and tend to show Ar 2 PO(H)⇌Ar 2 P(OH) tautomerism . The experimentally determined 1 H– 31 P coupling constants and 31 P resonances of 1 , 2 , and 3 indicated that these exist exclusively in the pentavalent Ar 2 PO(H) form.…”
Section: Resultssupporting
confidence: 85%
“…69,70 Diarylphosphine oxides are weak acids and tend to show Ar 2 PO(H)⇌Ar 2 P(OH) tautomerism. 71 The experimentally determined 1 H− 31 P coupling constants and 31 P resonances of 1, 2, and 3 indicated that these exist exclusively in the pentavalent Ar 2 PO(H) form. These characteristics can be attributed to the electron-donating character of aryl moieties attached to the P center as the electron-rich substituents on phosphorus can weaken the acidity of Ar 2 PO(H) and shift the equilibrium to the pentavalent side.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The P−O atomic distance measures 147.19 (11) pm, a reasonable value for P=O bonds (cf. Mes2P(O)H 148.54(13) pm), [48] however, significantly below the sum of the double bond covalent radii of oxygen and phosphorus (Σcov(P=O) = 159 pm [49] ) and nearly identical to the sum of the triple bond covalent radii of the respective atoms (Σcov(P≡O) = 1.47 Å [50] ). We kept attempting to determine the crystal structures of 1:Mes* as well as 1: Mes Ter, though unfortunately without success.…”
Section: Resultsmentioning
confidence: 95%
“…The P–O atomic distance measures 147.19(11) pm, a reasonable value for PO bonds ( cf. Mes 2 P(O)H 148.54(13) pm), 48 however, significantly below the sum of the double bond covalent radii of oxygen and phosphorus (∑ cov (PO) = 159 pm 49 ) and nearly identical to the sum of the triple bond covalent radii of the respective atoms (∑ cov (PO) = 1.47 Å 50 ). Whereas no suitable crystals could be grown for 1: Mes Ter , we were able to obtain small colorless needles from a hot, saturated MeCN solution of 1:Mes* .…”
Section: Resultsmentioning
confidence: 95%
“…47 The P-O atomic distance measures 147.19 (11) pm, a reasonable value for PvO bonds (cf. Mes 2 P(O)H 148.54(13) pm), 48 however, significantly below the sum of the double bond covalent radii of oxygen and phosphorus (∑ cov (PvO) = 159 pm 49 ) and nearly identical to the sum of the triple bond Scheme 1 An overview of aryl substituted phosphanylidenephosphoranes and their diverse reactivity. Phospha-Wittig reagents acting as phosphinidenoids (top) and nucleophiles (bottom).…”
Section: Introductionmentioning
confidence: 99%